(untitled) (International Journal of Environmental Sciences, 2025)
Emotional intelligence (EI) is essential for improving student learning experiences by increasing job satisfaction and decreasing burnout among teaching personnel. This study analyze the factors affecting the emotional intelligence of faculty in private universities of Himachal Pradesh. A questionnaire with a descriptive and exploratory research design was used to gather information from 402 faculty members. Employee resilience, self-awareness, professionalism, goal-setting, self-regulation, listening skills,empathy, observational abilities, optimism, perceived control, and gratitude are essential elements of emotional intelligence that were found through factor analysis.Higher education institutions should incorporate Emotional Intelligence focused training and assessment into their faculty development programs.